Pendampingan Literasi Keuangan Digital pada Pelaku Usaha Mikro Kecil dan Menengan (UMKM) dalam Meningkatkan Manajemen Usaha - Santoso, Haris; Iwannudin, Iwannudin (Universitas Islam Lamongan, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a contribution and role that is very important and important in the growth of the Indonesian economy. MSMEs are basically businesses run by individuals or families, so their customers are lower middle class people. In addition, there is a lot of evidence that MSMEs are more resilient than large corporations or large companies in the midst of the economic crisis that has hit. Digital transformation has brought significant changes to the ecosystem in doing business, including for Micro, Small and Medium Enterprises (MSMEs). Digital financial literacy is a key factor in increasing the efficiency of business management. This Community Service aims to provide an understanding and see the impact of digital financial literacy assistance on the management of MSME businesses in Metro City. The Community Service method used is Asset-Based Community Development (ABCD). Data was collected through interviews, observations, and documentation studies of MSME actors who participated in the digital financial literacy program. The steps and supporting efforts in the ABCD method approach process are search analysis to find appreciation, development and potential assets and program strategy analysis. The results of this community service show that increasing digital financial literacy has a positive impact on financial management, access to capital, and MSME competitiveness. Thus, digital financial literacy assistance can be an effective strategy in encouraging sustainable MSME growth for MSMEs in Metro City.